Implementation of The Hybrid Contract Model in Chilli Buying and Selling Transactions Between Farmers and Collectors From The Perspective of Islamic Economics (Case Study of Tegalan Village, Kandat District, Kediri Regency) - Widya Ratna Sari; Zuraidah (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2023)
This study aims to describe the Implementation of the Hybrid Contract Model in the Chilli Sale and Purchase Transaction between Farmers and Collectors in the Perspective of Islamic Economics in Tegalan Village, Kandat District, Kediri Regency. Based on qualitative research with the type of case study research. Data acquisition methods with focused open interviews. While data analysis: data reduction, data display, and data conclusions. The results of the study explain the application of the hybrid contract model in chilli buying and selling transactions carried out between farmers and collectors in Tegalan Village, Kandat District, Kediri Regency using a qard contract, wakalah contract, and sale and purchase contract. The implementation of the hybrid contract model in chili buying and selling transactions between farmers and collectors is not in accordance with the provisions of Islamic economics, namely the qard contract transaction mechanism which is not in accordance with sharia provisions because the pillars and conditions of qard have not been massively realised. The sale and purchase agreement used by farmers and collectors is Al-Bai' al-mu'ajjal. But in this case, the collectors when taking chillies to farmers do not provide a definite statement regarding tsaman (price). So that it indicates that the practice of buying and selling transactions carried out is not in accordance with sharia provisions. Meanwhile, the implementation of this wakalah contract is in accordance with sharia provisions.